Polifenoles y capacidad antioxidante en granos de cacao en función del genotipo y pisos altitudinales del cultivo en la zona 4 - Pincay Figueroa, Diana Marianella (2019)
Evaluating the polyphenolic content and antioxidant capacity in beans of three cocoa genetic materials at three altitudinal levels in zone 4 was the main objective of this research. Randomized samples of mature cobs from adult trees were collected from three cocoa genetic materials: TSE 103, National Complex x Trinitarians and CCN 51; in three altitudinal levels: low (14 masl), medium (165 masl) and high (379 masl). The experiment was developed under a DCA in factorial arrangement A (cocoa genetic materials) x B (altitudinal floors) with four replicas at a 95% confidence level. The higher polyphenolic content and the lower antioxidant capacity against the radical DPPH corresponded to the variant ETT- 103, in medium floor (165 msnm) and with respect to the interaction to ETT-103 with low floor (14 msnm) being thus established that the factors evaluated if they influenced significantly in the variables evaluated responses and additionally of determined an inverse correlation with a coefficient of determination R2 of 0.92 between them. It is concluded that the total polyphenolic content and its antioxidant capacity in cocoa varies with the genotype, the altitudinal floor of the crop, in addition, the antioxidant capacity decreases as the polyphenols increase.